Associations of active commuting and leisure-time physical activity with perceived cognitive function and work ability among Finnish employed adults: a population-based study - Jussila, Juuso J.; Pulakka, Anna; Appelqvist-Schmidlechner, Kaija; Ervasti, Jenni; Halonen, Jaana I.; Kalliolahti, Essi; Lahti, Jouni; Mikkonen, Santtu; Salo, Paula; Lanki, Timo (Springer Science and Business Media LLC, 2025)
BackgroundRegular active commuting - that is, walking or cycling to work - can improve cardiometabolic health and physical fitness among employed adults. This study aimed to examine whether regular active commuting is also associated with perceived cognitive function (memory function, learning ability, and concentration) and work ability. To explore potential differences across physical activity domains, these relationships were additionally assessed for leisure-time physical activity. MethodsThis study was based on cross-sectional data from the nationally representative FinHealth 2017 Study. Employed participants were categorised based on their commuting and leisure-time physical activity behaviour as either active or passive commuters and as sedentary, recreationally active, or exercisers and athletes, respectively. Covariate-adjusted quasi-Poisson regression was used to estimate relative risks (RR) with 95% confidence intervals (CI). For active commuting, dose-response analyses were also performed. ResultsAmong Finnish employed adults (N = 3525; mean age 45 years; 51% female), active commuting was not associated with perceived memory function, concentration, or work ability. However, active commuters had a 17% lower risk of suboptimal perceived learning ability compared to passive commuters (RR 0.83, 95% CI 0.70-0.99). In dose-response analyses, the association was observed only for lower volumes of active commuting (< 15 min a day; RR 0.67, 95% CI 0.50-0.89). Regarding leisure-time physical activity, exercisers and athletes had a 52% lower risk of suboptimal memory function (RR 0.48, 95% CI 0.38-0.60), a 54% lower risk of suboptimal learning ability (RR 0.46, 95% CI 0.36-0.60), a 49% lower risk of suboptimal concentration (RR 0.51, 95% CI 0.39-0.67), and a 65% lower risk of suboptimal work ability (RR 0.35, 95% CI 0.26-0.47) compared to sedentary adults. Similar associations were observed for recreationally active adults. ConclusionsActive commuting was associated with better perceived learning ability, suggesting that its benefits may extend to brain health. Leisure-time physical activity may have even greater potential for enhancing cognitive function and work ability among employed adults.